El pensamiento lateral, como característica no accesoria, dentro del aprendizaje implícito de las Ciencias Exactas (en inglés) - Basantes-Valverde, Williams; Tixi-Gallegos, Katherine; Allauca-Sandoval , Norma Isabel (Educación y sociedad, 2024)
Lateral thinking is the ideal way to achieve creativity within the student mentality; but to do so, it is essential to look at this challenge from another perspective. Reasoning skills are not only available thanks to advances in educational technology and rather, the solution to this dilemma must be based on the digital age; just like in the Knowledge Society. Therefore, this is how unconventional thinking will emerge as a social approach capable of allowing the independence of the Sciences and it is in this case that challenges, of Higher Education, will germinate by proposing permanent learning environments. Making every student work, collaboratively, in obtaining knowledge of the Exact Sciences and exemplifying with online courses that promote learning spaces; as long as intelligent software is the tool to interact.